Penambahan Carboxymethyl Celullose (CMC) Pada Susu Kacang Kenari (Canarium indicum, L.) Untuk Meningkatkan Stabilitas Emulsi dan Tingkat Kesukaan Panelis - Hizmadin, Ambar; Sumual, Maria Fransisca; Djarkasi, Gregoria S. S. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
This research was to determine the best CMC concentration treatment improve the stability of the emulsion and panelist acceptability milk of canarium nut. The study was based the RAL method with 5 treatments where A. 0% CMC, B. 0.4% CMC, C. 0.8% CMC, D. 1.2% CMC, and E. 1.6% CMC were then measured for emulsion stability, viscosity, total dissolved solids , pH measurement and panelist acceptability of canarium nut milk. The results of measuring the stability of the emulsion A. 0,22%, B. 0,17%, C. 0,11%, D. 0,06% and E. 0,03%. The viscosity of A. 21,26 cP, B. 30,18 cP, C. 36,65 cP, D. yaitu 37,63 cP, dan E. 41,24 cP. Total dissolved solids A. 8.53 ˚Brix, B. 8.83 ˚Brix, C. 12.53 ˚Brix, D. 13.23 ˚Brix and E. 13.96 ˚Brix. The pH value of A. 6.60, B. 6.65, C. 6.72, D. 6.73 and E. 6.80. Milk of canarium nut with a concentration of 1,6% CMC resulted in the most stable emulsion level with a creaming index value of 0,03%. The addition CMC to milk of canarium nut did not improve the panelist acceptability because the highest average was in the treatment without the addition of CMC (0% CMC) with a value of 4,90 (much prefer).